Disturbance of cytokine networks in Sjögren's syndrome - Youinou, Pierre (BioMed Central, 2011)
The difficulty in predicting the consequences of interactions between different cytokine networks has increased with the expansion of the T helper (Th) cell universe and the discovery of numerous B lymphocyte-derived cytokines. Consequently, it is now difficult to conceptualize a straightforward view of the contribution of these disturbances to the pathogenesis of primary Sjögren's syndrome (SS). Th1 cells, which produce interferon-γ and IL-2, and Th17 cells, which make IL-17 and TNF-α, have been cast in the leading roles of the play. However, the complex role of T-cell subsets in SS is accentuated by the reciprocal effects of Th17 cells and regulatory T cells found in salivary glands of SS patients. Furthermore, B lymphocyte polarization into type-1 B effector (Be1) and Be2 cells and B-cell modulating factors of the TNF family, most notably the B-cell-activating factor (BAFF), and their prominent role in SS are additional complicating factors. Whereas Th17 cells orchestrate autoreactive germinal centers, local BAFF would repress the generation of Th17 cells. Such new insights into interconnected cytokines in primary SS may lead to new treatments for these patients.